Processo de fragmentação e caracterização dos remanescentes de cerrado: análise ecológica da paisagem da bacia do rio dos Peixes (GO) - Carneiro, Gabriel Tenaglia (2012)
The occupation of the Cerrado in central Brazil is characterized by the increasing incorporation of new areas into production system at the expense of deforestation and conversion to agricultural use of their land, with the support of successive policies since the 1930s, but especially of the decade 1970, induced by the Polocentro Cerrado Development Program, when this process was intensified, causing fragmentation and isolation of the remnants of its various vegetation types. This thesis presents the results of the studies of basin Peixe fiver, a member of the upper basin of the Araguaia River, in the state of Goiás between 1970 and 2009, based on an approach in Ecology Landscape, Geography and Botany (Floristic) applied to the theme of fragmentation of vegetation. The overall goal is to identify and to characterize the remnants and their relations with the evolution of land use and soil types in order to provide data for the evaluation of conservation and sustainability. Methodologically, it employs geo technologies, analysis of landscape metrics and floristic composition of representative fragments beyond the analysis of the relation between land use, soil types and spatial distribution of remaining with emphasis on Principal Component Analysis. The results revealed high rates of current deforestation and increasing fragmentation between 1985 and 2009, and risk, threat to biodiversity conservation. Also revealed predominance of the relation between Ultisols and Pastures interpreting it as a result of the intermediaries agricultural potential of these soils for intensive cultivation due to its high fragility associated with the high erodibility, which would burden other forms of much use, and emphasize concentration of the remaining in areas Permanent Preservation (APP) in the pastures, especially Riparian Forest, more continuous and with greater floristic richness. It was concluded that expand in cattle raising in the studied area was strongly influenced by the soil factor, the low potential of cultivation, which could also explain the lower rate of conversion of the Cerrado, caused by the use anthropic when compared to neighboring basins, where better soils and softer dominated reliefs and softer, and finally the remnants fragments are still recoverable due sustainability indicators revealed by their metrics. Keywords: